The Role of Sports Spirit in Ideological and Political Teaching in Cultivating Students’ Psychological Resilience - Xiaoqiang Xu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The psychological resilience of college students is compromised in various dimensions, including cognition and willpower, owing to the adverse influences of media and multicultural factors. This underscores the pressing need for colleges and universities to bolster the cultivation of psychological resilience among the new generation of college students through ideological and political education. Consequently, enhancing students' capacity to withstand pressure, fostering teamwork and interpersonal communication skills, and nurturing psychological resilience as a secondary personality trait become imperative objectives. Therefore, the study aims to investigate the role of sports spirit within ideological and political teaching in cultivating students' psychological resilience. This study examines the effects of an ideological and political curriculum program on 102 freshmen and sophomores at a university. The program integrates human education motivation (teacher and group education motivation) and physical education motivation into the curriculum. Psychological resilience among college students, comprising factors such as motivation, positive cognition, teacher support, and interpersonal support, is assessed. Throughout the program, human and material education factors serve as driving forces, creating a comprehensive network of ideological and political education within and beyond the classroom, fostering character development through direct and indirect education methods. The judgment coefficient R2 ranged from 0.513 to 0.575, and R2=0.742 showed that there was a certain linear correlation between the variables. The regression coefficients of human fertility dynamics were 0.550, 0.699, 0.802 and 0.753 (P<0.001), and the regression coefficients of physical fertility dynamics were 0.245 and 0.172 (P<0 05), accept the original hypothesis that H1, H2, H3, H5, H7 and H8 have a positive impact. The utilization of the "curriculum ideological and political" and the administration of psychological resilience questionnaires among college students exhibit commendable reliability and validity. Within the framework of the "curriculum ideological and political," motivation stemming from physical education demonstrates a positive correlation with two dimensions of psychological resilience, while humanistic education motivation shows a positive correlation with all four dimensions of psychological resilience. The incorporation of sports spirit into ideological and political education assumes a pivotal role in fostering students' psychological resilience. Sports spirit, characterized by traits such as perseverance, teamwork, initiative, and self-challenge, closely aligns with the development of psychological resilience. Consequently, the amalgamation of sports ethos within ideological and political teaching empowers students to enhance their psychological resilience, enabling them to confront challenges, persevere, and adapt, thereby contributing to their holistic growth and character development. By emphasizing values inherent in sportsmanship, including teamwork, discipline, and determination, students acquire essential life skills, facilitating their navigation through setbacks, adversity, and emerging strengthened both academically and personally.